2018
DOI: 10.1097/md.0000000000009323
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative clinicopathological factors affecting cervical adenocarcinoma

Abstract: Currently, cervical adenocarcinoma (ADC) receives the same standard treatment as squamous cell carcinoma, but this treatment regimen is not wholly suited for ADC. The present study was conducted to assess the prognostic role of postoperative clinicopathological factors in patients with stage I–IIB cervical ADC.The study examined 312 patients with stage I–IIB cervical ADC who underwent radical hysterectomy, including pelvic lymphadenectomy, at our institutions between October 2006 and September 2014. Overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…According to many studies, patients with ADC exhibit worse survival outcomes than patients with SCC [ 17 18 ]. The Japan Society of Obstetrics and Gynecology collected and analyzed data from 15,698 patients with cervical cancer, and found that patients with SCC had a significantly better prognosis than patients with ADC (p=0.004); the 5-year OS rates were 80.4% and 75.7% for patients with SCC and ADC, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to many studies, patients with ADC exhibit worse survival outcomes than patients with SCC [ 17 18 ]. The Japan Society of Obstetrics and Gynecology collected and analyzed data from 15,698 patients with cervical cancer, and found that patients with SCC had a significantly better prognosis than patients with ADC (p=0.004); the 5-year OS rates were 80.4% and 75.7% for patients with SCC and ADC, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with some previously reported research findings. A study has shown that the factors affecting the prognosis of cervical adenocarcinoma include histological grade, lymph node metastasis, and tumor size (7). Another study has pointed out that the prognosis of cervical adenocarcinoma patients with late International Federation of Gynecology and Obstetrics (FIGO) stage, local tumor diameter >4 cm, and poor tumor cell differentiation is poor (20).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical variables cannot accurately predict the prognosis of patients with cervical cancer, and there is controversy among the results of various studies. A study pointed out that the depth of invasion and histological grade are related to prognosis (7). Research also emphasized that the clinical factors of cervical adenocarcinoma lack specificity, and only lymph node metastasis is an independent risk factor for the prognosis of cervical adenocarcinoma (8).…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence rate of cervical cancer has shown an overall decrease [21], the incidence rate of UAC has increased [22]. At present, the main treatment of UAC remains radical surgery or CCRT, but the sensitivity of UAC to radiotherapy is lower than that of SCC [23], and the survival outcomes of UAC patients are worse than SCC patients [24,25]. Therefore, more patients with UAC undergo surgery.…”
Section: Discussionmentioning
confidence: 99%